A Qualitative Approach on Nurse Turnover Intention of Private Hospitals in Cileungsi, Indonesia - Maryanti, Dianingsih; Erni, Nofi; Mutiara, Rina (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Turnover is one of the human resources risks that hospital management should address to maintain the number of nurses at private hospital. Objective: This study aims to explore factors that influence the turnover intention of nurses in private hospitals in Cilengsih, Indonesia. Method: A qualitative phenomenological approach was applied in this study. Ten informants were selected using a purposive sampling technique which was based on inclusion criteria. Result: the results of the study show that the causes of nurse turnover intention are such as 1) high gap of salary among nurses who have worked for a long time with new nurses; 2) Nurse's personal attitude and characteristics; 3) conflicts with colleagues or family; and 4) A better offer than other places or competing hospitals. Conclusion: This study conclude that there are 4 factors that cause high nurse turnover in private hospitals. Recommendation: workload analysis, career management and nurse job satisfaction surveys need to be carried out by hospital management to prevent high nurse turnover in hospitals